Stereoselective Desymmetrization Methods in the Assembly of Complex Natural Molecules - Sharpe, Robert.J.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This thesis describes the inception, design, and implementation of stereoselective desymmetrization reactions in the total synthesis of the natural products pactamycin and paspaline. In the case of pactamycin, the author develops a novel asymmetric Mannich reaction and symmetry-breaking reduction strategy to enable facile construction of the complex core architecture in fifteen steps using commercially available materials - the shortest synthesis to date. He subsequently demonstrates the flexibility of this approach in SAR investigations by highlighting the preparation of twenty-five unique pactamycin structural congeners. For paspaline, the author develops a biocatalytic desymmetrization strategy that allows the highly controlled synthesis of core stereochemistry and provides a platform for the development of new conceptual disconnections in the synthesis of "steroid-like" natural products. This thesis offers a valuable resource for students embarking on a PhD in total synthesis.
Asymmetric Synthesis Of The Aminocyclitol Pactamycin, A Universal Translocation Inhibitor -- Preparation And Biological Evaluation Of Synthetic and Polymer-Encapsulated Congeners of the Antitumor Agent Pactamycin: Insight Into Functional Group Effects and Biological Activity -- Inception and Development of a Global and Local Desymmetrization Approach to the Synthesis of Steroidal Alkaloids: Stereocontrolled Total Synthesis of Paspaline.
Keywords: Chemistry, Organic; Medicinal chemistry; Chemistry, Technical; Organic Chemistry; Medicinal Chemistry; Industrial Chemistry